Procurement, Reform, Accountability, and Internal Control: Effects on Budget Absorption - Lemana, Alifia Harfiani; Handarini, Dwi; Pahala, Indra (Universitas Pamulang, 2025)
This study analyses the effect of goods/services procurement, bureaucratic reform, public accountability, and the Government Internal Control System (SPIP) on budget absorption in Ministries and State Institutions in Indonesia. This research was conducted with quantitative methods through multiple linear regression analysis to see the effect of independent variables on the dependent variable, and robustness tests to test the robustness of the model used. The results showed that public accountability has a significant effect on budget absorption, indicating that transparency and public accountability encourage the effectiveness of budget management. In contrast, the procurement of goods/services, bureaucratic reform, and SPIP had no significant effect on budget absorption. This is due to the revision of the Budget Implementation List (DIPA), bureaucratic reforms that focus more on administrative efficiency, and the implementation of the Government Internal Control System, which is not yet optimal. The results of this study are expected to provide insights for policymakers in improving budget absorption in the government sector.